(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective The variation of iron status with the occurrence of acne vulgaris is not clarified and requires further investigation. Additionally, biochemical indicators such as magnesium, lactate, and lactate dehydrogenase activity (LDH) need to be adequately studied in acne patients. The aim of this study was to detect the association of acne vulgaris with iron parameters, gender, magnesium (Mg), lactate, and lactate dehydrogenase (LDH) in adolescents and young adults compared to a control group. Material and methods The study was conducted at the laboratory of Vin Private Hospital in Duhok, Iraq from March to November 2023. The study measured the levels of iron, unsaturated iron binding capacity (UIBC), Mg, lactate, and LDH in the serum samples of 200 individuals. The total ironbinding capacity (TIBC) and transferrin saturation (TS) were calculated mathematically. The study population consisted of 100 individuals diagnosed with acne vulgaris in the dermatology unit at Azadi Teaching Hospital, who were further subdivided into 28 mild, 44 moderate, and 28 severe cases, as well as 100 age- and sex-matched healthy controls selected from secondary schools and university students. Statistical analyses were performed using SPSS version 25 for Windows. A p-value less than 0.05 was considered statistically significant. Results and discussion Iron, TIBC, UIBC, Mg, and LDH levels were significantly increased in the patient group. Logistic regression analyses showed that TIBC and LDH associated with acne vulgaris, with odds ratios of 1.019 and 1.023, respectively. The areas under the ROC curves for TIBC and LDH were 0.808 (95% CI 0.745-0.871) and 0.829 (95% CI 0.771- 0.888), respectively, which was statistically significant. The cutoff values for TIBC and LDH were 309.3 and 197.2, respectively. Multiple comparisons showed no significant differences in iron parameters, Mg, lactate, and LDH activity among the patient subgroups. Conclusion The abnormalities in iron status observed in patients with acne vulgaris, such as elevated total iron levels coupled with increased TIBC, along with elevated LDH, could serve as potential markers indicating the onset of acne vulgaris and concurrent hemolysis. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 589-597